DIMENSIONAL ACCURACY OF DIGITAL IMPRESSION AND DOUBLE IMPRESSION MOLDING MODELS IN THE MANUFACTURING OF BRIDGE DENTAL : AKURASI DIMENSI MODEL HASIL CETAKAN DIGITAL IMPRESSION DAN DOUBLE IMPRESSION DALAM PEMBUATAN GIGI TIRUAN JEMBATAN - Suhendra; Dewi Farida Nurlitasari; Dsk Pt Bunga Raditya Pradnyadena (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2022)
Dimensional accuracy of the impression model is very important in determining the success of denture treatment. The choice of printing technique is a factor that has a big influence on the printout. Digital impression and double impression techniques have good dimensional stability and provide accurate print details on the working model. The purpose of this study was to determine the level of dimensional accuracy of the digital impression and double impression models in the manufacture of bridge dentures. The research materials used were polyvinyl siloxanes elastomeric impression materials, stone gypsum type IV and aquades. The tools used are the master model, physiological printing spoon, glass stirrer, lekron, bowl spatula, calipers and 3D laser scanner. This research method used a laboratory experimental study design, and the master model was imprinted on the simulation of two abutments using digital impression and double impression techniques. The results showed that the digital impression technique showed a significant difference measured from the mesiodistal distance with the smallest value -0.004, the largest 0.011, the average difference 0.0369, at the occlusogingival distance the smallest value -0.003, the largest 0.009, the average difference 0.0375 , and the smallest value of interbutment distance is -0.001 and the largest is 0.000, and the average difference is -0.00031. The double impression technique showed a significant difference measured from the mesiodistal distance, the smallest value was -0.004, the largest was 0.011, the average difference was 0.00663, at the occlusogingival distance the smallest value was -0.014, the largest was 0.003, the average difference was 0.00300, and the interabutment distance was the smallest -0.001, the largest 0.003, and the average difference 0.00044. The conclusion of this study is that the digital impression technique is more accurate than the double impression technique in making denture bridges.